Two Sides: Development of Non-Bank Islamic Financial Institutions in Indonesia - Cahyani, Binda Rahma; Arif, Muhammad; Sudirman, Wahyu Febri Ramadhan; Fithriyana, Rinda; Reza, Saru (Journal of Financial and Business, 2025)
This study aims to identify challenges and opportunities in developing Non-Bank Islamic Financial Institutions (LKSNB) in Indonesia. With the increasing public interest in Sharia-based financial services, LKSNB has great potential to become an important pillar in supporting the growth of the sharia economy. The research method used is literature study and descriptive analysis, regarding secondary data from various reports of related institutions and academic literature. The results of the study indicate that the main challenges faced by LKSNB include low sharia financial literacy among the public, regulations that do not fully support the development of LKSNB, and limited human resources who have special competence in the field of sharia finance. On the other hand, great opportunities arise from the growth of the global sharia economy, government support through various policies, and increasing public awareness of the importance of a financial system based on sharia principles.